SUPERVISI AKADEMIK TERHADAP KOMPETENSI PEDAGOGIK GURU PADA MASA PANDEMI COVID-19 - Muhamad Alwi (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2021)
The purpose of this study is to describe the planning, implementation, evaluation, and follow-up of academic supervision carried out by the Madrasah Head on the pedagogical competence of teachers at MA Istiqlal Jakarta during the pandemic in March 2021. This study uses a qualitative research method of case study type with interactive data analysis techniques. . Data collection techniques include interviews, observation, and documentation. The results showed that: 1) Academic supervision planning: the head of the madrasah makes a supervision schedule, informs teachers regarding the supervision schedule, supervision instruments; 2) Implementation of academic supervision: conducted through observation and interviews using the zoom meeting platform; 3) Evaluation of supervision: there is still no compatibility between the assessment of the lesson plans and the implementation of teaching teachers, there is less variety of teachers in choosing learning media, teachers are not fully engaged in apperception activities at the beginning of learning; 4) Follow-up on academic supervision: dissemination by teachers to peers about the results of supervision, fostering teacher competence in managing virtual learning through training on learning models. The results of academic supervision are used as a reflection guide in improving the pedagogic competence of teachers.